2016
DOI: 10.1177/1073191116632336
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Exploratory Factor Analysis of the Feeling Word Checklist–24

Abstract: Emotional reactions are a vital part of the therapeutic relationship. The Feeling Word Checklist-24 (FWC-24) is an instrument asking the clinician (or the patient) to report to what degree he or she has experienced various feelings during a therapeutic interaction. The aim of this study was to assess the factor structure of the clinician-rated FWC-24 when taking dependencies in the data into account. The sample was deliberately heterogeneous and consisted of 4,443 ratings made by 101 psychotherapists working w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 38 publications
6
40
0
Order By: Relevance
“…The mean scores range from 0.47 (Inadequate) to 1.12 (Idealised) to 2.74 (Confident).. The scores are in a similar range to that seen in many other FWC studies-that is, quite low scores are consistently reported (9,14,17,18). However, the patients in the present study are mainly poorly functioning PD patients, and one might have expected stronger feelings to be reported.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The mean scores range from 0.47 (Inadequate) to 1.12 (Idealised) to 2.74 (Confident).. The scores are in a similar range to that seen in many other FWC studies-that is, quite low scores are consistently reported (9,14,17,18). However, the patients in the present study are mainly poorly functioning PD patients, and one might have expected stronger feelings to be reported.…”
Section: Discussionsupporting
confidence: 85%
“…Generally, all studies have found at least one factor reflecting positive feelings and at least one reflecting negative feelings (9). One goal in the CT research is to find many of the same feeling factors, as this may support that important aspects of CT have been captured.…”
Section: The Fwcmentioning
confidence: 99%
See 3 more Smart Citations